Could the rhizoplane biofilm of wetland plants lead to rhizospheric heavy metal precipitation and iron-sulfur cycle termination? - Li, Yuanyuan; Feng, Wenling; Chi, Haochun; Huang, Yunxi; Ruan, Dishen; Chao, Yuanqing; Qiu, Rongliang; Wang, Shizhong (Journal of soils and sediments, 2019)
Purpose Iron plaque (IP) formation via radial oxygen loss (ROL) of wetland plant has been predominantly recognized as the reason for heavy metal sequestration in the rhizosphere. However, the same contribution of the microbes living in a potential rhizoplane biofilm matrix has not been comprehensively elucidated. In this review, we proposed a conceptional model of the wetland plant rhizoplane biofilm and summarized the possible pathways therein for heavy metal precipitation and iron-sulfur cycle termination. Materials and methods After an introduction of the effects of IP and microbes on the phytoremediation of heavy metal-contaminated wetland, the distribution of rhizospheric bacteria and different metal speciations resulted from wetland plant ROL were demonstrated. Based on the studies of microflora in the rhizosphere and IP, coupled with the ROL nature, we proposed an existence of rhizoplane biofilm with a special structure that could contribute to the rhizospheric iron-sulfur cycle termination by the production of heavy metal precipitates (metal sulfides). Results and discussion The ROL leads to the diffusion of oxygen with a decreasing gradient from the root surface (rhizoplane) to the bulk soil, allowing the formation of an unconventional rhizoplane biofilm comprising an aerobic inner layer and an anaerobic outer layer. Thus, aerobic bacteria, e.g., iron-oxidizing bacteria (IOB) and sulfur-oxidizing bacteria (SOB), as well as anaerobic bacteria, e.g., iron-reducing bacteria (IRB) and sulfate-reducing bacteria (SRB), are favored in the inner layer and outer layer of the rhizoplane biofilm, respectively. In the inner layer, ferrous sulfide is oxidized by IOB and SOB to Fe 3+ and SO 4 2− . Fe 3+ is thereafter bound with oxygen into iron (hydro)oxides, aggregating into a barrier of iron plaque for heavy metal sequestration and O 2 diffusion. Excessive SO 4 2− diffused to the outer layer is reduced to S 2− by SRB, forming sufficient metal sulfide precipitates that on one hand immobilize those heavy metal ions released by H + , and on the other hand serve as a barrier for preventing the contact of ferrous sulfide from O 2 . Hence, further oxidization of ferrous sulfide is terminated. Conclusions This rhizoplane biofilm co-existing with IP contributes to the rhizosphere element circulation. Further investigation and demonstration of its composition, structure, and function will help us better interpret the survival strategy and bioremediation potential of wetland plants in flooded mining areas, such as mine tailing ponds in tropical and sub-tropical regions with abundant rainfall.